2022
DOI: 10.1021/acs.analchem.2c02086
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Scope of Targeted Metabolomics by One-pot Microscale Synthesis and Tailored Metabolite Profiling: Investigation of Bile Acid–Amino Acid Conjugates

Abstract: Accurate metabolite characterization plays a vital role in targeted metabolomics. Nonetheless, the library of metabolites is still limited, especially for downstream conjugates, and it is time-consuming to synthesize each of these compounds due to high structural diversity. Herein, a green and smart strategy was developed to expand the scope of targeted metabolomics. The reference standards were synthesized in a one-pot microscale reaction, and the analytical method was tailored using the synthetic products. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Notably, an additional 48 12HBA candidates were further extracted through the untargeted screening function of the 12α-HSDH-assisted LC-HRMS method. Nine of them coincided with newly discovered amino acid-conjugated BAs (AA-BAs). This finding showcased the capability of our strategy in discovering new metabolites. However, it is important to clarify that AA-BAs were not included in the theoretical database.…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Notably, an additional 48 12HBA candidates were further extracted through the untargeted screening function of the 12α-HSDH-assisted LC-HRMS method. Nine of them coincided with newly discovered amino acid-conjugated BAs (AA-BAs). This finding showcased the capability of our strategy in discovering new metabolites. However, it is important to clarify that AA-BAs were not included in the theoretical database.…”
Section: Resultsmentioning
confidence: 59%
“…31 To examine the chromatographic behavior of available BA references under our chromatographic condition, we chemically synthesized an additional 64 BAs (Table S9 and Supporting Information). 34 Surprisingly, we found that the ΔRT between glyco-BAs/tauro-BAs and their matching free BAs is not constant but rather exhibits a proportionality to the RT of free BAs. The linear correlation between ΔRT and RT for free-BAs is presented in Figure S11, with R 2 values (coefficients of determination) of 0.9784 and 0.9804 for tauro-BAs and glyco-BAs, respectively.…”
Section: Construction Of a Multidimensional Bas Profile Directed By 1...mentioning
confidence: 99%
“…UPLC parameters were modified from the method of ref. 39 . LC–MS/MS analyses were performed using a Vanquish ultra-high-performance liquid chromatography system coupled with a TSQ Quantis Plus mass spectrometer (Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the gut microbiota is also reported to enrich the diversity of the second BAs structures through four pathways: deconjugation of glycine or taurine, dehydrogenation, dehydroxylation, and epimerization [ 8 , 9 , 10 , 11 ]. Recently, some novel amino-acid-conjugated BAs, other than nor-DCA, tetra-BAs, 3,7,12,24-tetrol-26,27-dinorcholetane-24-sulfate, have been mined in gut microbiota metabolism, which further enrich the diversity and composition of the BA pool [ 12 , 13 , 14 ]. Regarding the free BAs, oxidation frequently occurs at C-3, C-6, C-7, and C-12 sites.…”
Section: Introductionmentioning
confidence: 99%